PORTFOLIOS AS ASSESSMENT TOOLS FOR BASIC SPEAKING LESSON: ITS USEFULNESS IN HIGHER EDUCATION - Siti Maria Ulfa (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2019)
Abstract. Portfolio is method which is alternatively can be used to assess students’ ability in English. This study, therefore, aimed to investigate the usefulness of using portfolios as assessment tools in Basic Speaking lesson in higher education. The data were two lecturers who are teaching Basic Speaking in English Education Department. The data were then analyzed qualitatively since this study observe the natural phenomena happen in English language teaching and interview was also used to obtain more information both from students and lecturers. The results revealed several things, such as portfolios provide students to see their own strengths and weaknesses when they produced the tasks, also provide students to look at closer their own learning within a unique way and hereafter as their critical self-analysis, and last but not least, it provides many information both from the students as their language learning process and lecturers enable to impersonate the process of teaching.